Health Care Professionals’ Pain in Pandemic COVID 19 in India (Medico Legal Update, 2020)
Health care professionals are highly vulnerable for COVID 19 infection. It is due to frequents contact withCOVID 19 positive patients, long time exposure with positive patients. There may be lack of personnelprotective equipment’s (PPE).Indian health care professional taking many kinds of pain during themanagement of COVID 19.it can be hospital related problems during management, professional must wearPPE about 06 hours on duty time. Duty time with PPE personnel uncomforted and cannot have anythingeven water. PPE cannot change frequently. Sociallypersons do not comfort because society not accepting asnormal people,they afraid of spreading of corona by health care personnel. Family isolation also necessaryfor the health care professional to avoid infection to their family members during COVID 19 management.Healthprofessionals have tough time to managepandemic. Government also active and full swing supportingproviding extra care of health professionals. giving insurance and approved extra budget to fight withCOVID 19.